A mesoporous UiO-67 coated Zn or Cu particle catalyst and its preparation method and application

Through the preparation method of mesoporous UiO-67 encapsulated Zn or Cu particles catalyst, the problems of uneven metal particles in UiO-67 material and the catalytic activity decrease are solved, and the stability and reusability of the catalyst are achieved, which significantly improves the two Conversion and selectivity of chlorinated vinyl carbonate.

CN118649710BActive Publication Date: 2024-12-17SHANDONG HAIHUA GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411117812.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the complete encapsulation of metal particles and uniform dispersion of UiO-67 materials, resulting in the problem of decreasing catalytic activity and falling off metal particles. Especially in the catalytic reaction of dichlorovinyl carbonate, metal particles are prone to agglomeration, inactivation, recycling and reuse. Low.

Method used

The preparation method of mesoporous UiO-67-encapsulated Zn or Cu particles is adopted. Through ultrasonic dissolution and solvothermal reaction, the concentration of polyvinylpyrrolidone and metal cations is controlled, and the solvent-heat etching reaction is carried out using pore-forming agent solution to form a mesoporous structure. , ensure that the metal particles are completely wrapped and evenly distributed by UiO-67.

Benefits of technology

The stable wrapping and uniform distribution of metal particles is achieved, catalytic activity and acid resistance are improved, the stability and reusability of the catalyst are ensured, the catalytic effect is significantly improved, and the conversion rate and selectivity of dichlorovinyl carbonate are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118649710B_ABST
    Figure CN118649710B_ABST
Patent Text Reader

Abstract

The present invention provides a mesoporous UiO-67-wrapped Zn or Cu particle catalyst and its preparation method and application, belonging to the technical field of material preparation. The present invention first synthesizes Zn or Cu particles, then in-situ synthesizes UiO-67, and finally reacts with solvent thermal etching of a pore-forming agent solution. By adjusting the concentration, reaction time and temperature of the reactants, Zn or Cu particles and UiO-67 and mesoporous UiO-67 can be obtained to wrap Zn or Cu particle catalysts, and retain the morphology and framework structure of UiO-67 itself. The catalyst size of the present invention is 1-2.5 μm, the pore size range is 5-50 nm, the Zn or Cu particle size is 20-70 nm, and the Zn or Cu particles account for 3-8% of the catalyst mass. The synergistic effect of its mesoporous structure and Zn or Cu particles and the etching reaction expose more active sites of the catalyst, which is applied to the catalytic field of preparing vinylene carbonate from dichloroethylene carbonate, and the conversion rate of dichloroethylene carbonate is more than 85%, and the selectivity of vinylene carbonate is more than 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and specifically relates to a mesoporous UiO-67-coated Zn or Cu particle catalyst, and a preparation method and application thereof. Background Art

[0002] Metal particles (NPs) have attracted great attention due to their easy recycling and high catalytic efficiency. However, free metal nanoparticles have high surface energy and are prone to agglomeration during catalytic reactions. To overcome these shortcomings, encapsulation with shells is one of the most commonly used methods to protect the stability of NPs.

[0003] Metal-organic frameworks (MOFs) are a new type of highly porous crystalline materials that can accommodate nanoparticles of various sizes and shapes and are mostly used in heterogeneous catalysis. UiO-67 is the most representative UiO series material, which has high acid resistance, special topological structure, excellent thermal and chemical stability, high specific surface area, abundant active sites and adjustable pore structure. It has broad application prospects in the fields of heterogeneous catalysis, gas adsorption and separation.

[0004] For UiO-67 encapsulated metal particles, most people first synthesize UiO-67 materials and then add metal salt solutions to perform post-synthesis modified solvent thermal reactions to obtain UiO-67 materials after metal cation exchange, and finally add reducing agents such as sodium borohydride or use high-temperature pyrolysis to treat the UiO-67 materials after metal cation exchange. However, this method obtains UiO-67 materials loaded with metal particles, not UiO-67 materials wrapped with metal particles. Of course, during the reaction process, some metal particles will enter the interior of the UiO-67 material channels. This is mainly because the UiO-67 material itself has an adsorption effect (after the catalyst is washed multiple times or desorbed at high temperature, the adsorbed metal particles will fall off, and the metal particles cannot be immobilized). Therefore, exploring a catalyst preparation method in which a UiO-67 material completely encapsulates metal particles inside and the metal particles are evenly dispersed inside the UiO-67 is of great research significance in the field of catalysis.

[0005] UiO-67 material is a microporous material, and its pores limit its application in the field of catalysis. Existing methods for preparing porous materials include pyrolysis, acid-base etching, template method, and solvent thermal method. The pyrolysis method is to calcine the UiO-67 material at high temperature to change its structure to obtain a porous UiO-67 material, but it has high energy consumption and will change the structure of the UiO-67 material; the acid-base etching method is to place the UiO-67 material in an inorganic acid or strong alkali solution such as hydrochloric acid or sulfuric acid. Compared with the pyrolysis method, this method is easier to obtain and maintain the structure of the UiO-67 material, but it will seriously damage the morphology of the UiO-67 material. The prepared UiO-67 material is often a macroporous material, and the reaction process is not easy to control; the template method is to add templates such as polystyrene balls to the UiO-67 material, and then remove the templates such as polystyrene balls by post-treatment, but the operation is cumbersome and not easy to industrialize; the solvent thermal method is to directly add the pore-forming agent solution to the reaction, and the pore-forming agent solution and the surface of the UiO-67 material are etched to produce defects. The reaction is simple to operate and easy to industrialize. So far, the structure of mesoporous UiO-67 encapsulated Zn or Cu particle materials has not been seen.

[0006] The Chinese invention patent document with the publication number CN104128603A discloses a metal nanoparticle wrapped in a zirconium-based porous shell and a preparation method thereof. The method uses metal nanoparticles as the core, and by adjusting the concentrations of polyvinyl pyrrolidone and zirconium precursors and organic ligands, in-situ synthesis is performed to obtain materials with different degrees of thickness of zirconium-based porous materials wrapped around metal nanoparticles, but the method destroys the morphology (octahedron) and structure of the zirconium-based porous material itself; the patent proves that the surface of the metal particles is a zirconium-based porous material through Raman. Since the essence of Raman characterization is to detect carbon-containing functional groups, the characterization only proves that the surface of the metal particles contains organic ligands of zirconium-based porous materials, and does not mean that the surface of the metal particles is a zirconium-based porous material. In addition, the scanning electron microscopy characterization of the metal nanoparticles wrapped in the zirconium-based porous shell shows that the shell of the material is an amorphous morphology. Combined with the above Raman test results, it can be seen that the patent actually obtains materials with different thicknesses of organic ligands wrapped around metal nanoparticles, not nanoparticles wrapped by zirconium-based porous materials.

[0007] The Chinese invention patent document with publication number CN116892029A discloses a metal organic framework material wrapped copper zinc bimetallic catalyst and its preparation method and application. The patent synthesizes copper zinc nanoparticles first, then synthesizes metal organic framework materials, and then adds the copper zinc nanoparticles to a solvent containing metal organic framework materials and immerses them for a period of time to obtain a metal organic framework material wrapped copper zinc bimetallic catalyst. The essence of this patent is that the metal organic framework material is used to obtain a bimetallic catalyst loaded with metal nanoparticles by an impregnation method, but the metal organic framework material cannot be used to wrap the copper zinc bimetallic nanoparticle catalyst, and there is no characterization method such as XRD and TEM to further prove that the catalyst belongs to an encapsulated structure.

[0008] The Chinese invention patent document with publication number CN112642487A discloses a UiO-67 encapsulated metal nanoparticle catalyst and its preparation method and application. The patent first synthesizes UiO-67, then adds UiO-67 to a solution containing a metal salt and immerses it for a period of time, and finally puts the impregnated UiO-67 into a reducing atmosphere for calcination to obtain a UiO-67 encapsulated metal nanoparticle catalyst. The essence of the patent is to load metal nanoparticles on the surface of UiO-67 by impregnation and thermal decomposition of reducing gas. The metal nanoparticles are not inside UiO-67, but only on the surface of UiO-67. In addition, since the thermal decomposition method uses high-temperature calcination, it will cause the agglomeration of metal nanoparticles, thereby causing a decrease in catalyst activity.

[0009] The Chinese invention patent document with publication number CN111111784A is a UiO-67-coated Co catalyst and its preparation method and application. The patent first obtains a cobalt salt ligand after two solvothermal reactions and one pH adjustment reaction, then the cobalt salt ligand is subjected to a solvothermal reaction of ion exchange with a zirconium salt, and finally a high-temperature pyrolysis reduction reaction is performed to obtain a UiO-67-coated Co catalyst. The preparation method is very complicated. It involves two solvent thermal reactions, one pH adjustment, and one ion exchange reaction. The preparation process route is too long, which increases the process cost. The ion exchange reaction between the zirconium salt and the cobalt salt ligand in this method is difficult to control. This is because the reaction process involves the transformation of the cobalt salt ligand organic matter into the UiO-67 structure. Only when zirconium and cobalt undergo ion exchange can the UiO-67 material be formed. However, the patent does not contain characterization methods such as XRD to prove that the UiO-67 material is obtained. Therefore, the method may obtain a zirconium-doped cobalt salt ligand organic matter, not a UiO-67 material. In addition, step (3) of the patent requires the reduction of cobalt ions at a high temperature of 300-400°C. During the high-temperature reaction process, the cobalt metal nanoparticles will agglomerate, thereby causing the catalytic activity of the catalyst to decrease. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a mesoporous UiO-67 coated Zn or Cu particle catalyst and a preparation method and application thereof, aiming at the problem that metal particles are easy to agglomerate, deactivate and have low recycling and reuse in the catalytic reaction of ethylene dichloride carbonate; the method has simple process, good repeatability and mild reaction, retains the morphology and framework structure of UiO-67, and forms a new mesoporous structure; the mesoporous UiO-67 coated Zn or Cu particle catalyst shows excellent catalytic activity in the catalytic application of synthesizing vinylene carbonate from ethylene dichloride carbonate.

[0011] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0012] First of all, the first technical problem solved by the present invention is to provide a mesoporous UiO-67 wrapped Zn or Cu particle catalyst with a pore size range of 5-50nm, the mesoporous UiO-67 completely wraps the Zn or Cu particles, the size of the mesoporous UiO-67 is 1-2.5μm, the size of the Zn or Cu particles is 20-70nm, and the Zn or Cu particles account for 3-8% of the catalyst mass. It is a white powder catalyst with Zn or Cu particles as the core and mesoporous UiO-67 as the shell structure.

[0013] Secondly, the second technical problem to be solved by the present invention is to provide a method for preparing a mesoporous UiO-67-coated Zn or Cu particle catalyst, comprising the following steps:

[0014] (1) dissolving zinc chloride or copper chloride and polyvinyl pyrrolidone in an amine polar organic solvent and ultrasonically dissolving them to prepare a first mixed solution; dissolving ascorbic acid in an amine polar organic solvent and ultrasonically dissolving them to prepare a second mixed solution; adding the second mixed solution to the first mixed solution, stirring at room temperature for 0.5-2h, centrifuging, washing, and vacuum drying to obtain Zn or Cu particles;

[0015] (2) adding Zn or Cu particles, 4,4'-biphenyldicarboxylic acid, and polyvinyl pyrrolidone to N,N-dimethylformamide, and uniformly mixing by ultrasonication to prepare a third mixed solution; dissolving zirconium oxychloride or hafnium oxychloride in N,N-dimethylformamide by ultrasonication to prepare a fourth mixed solution; adding the fourth mixed solution to the third mixed solution, and then reacting in a closed state; after the reaction is completed, centrifuging, washing, and vacuum drying to obtain UiO-67-coated Zn or Cu particles;

[0016] (3) UiO-67-coated Zn or Cu particles are added to a pore-forming agent solution for a solvothermal reaction. After the reaction is completed, the catalyst is centrifuged, washed, and vacuum dried to obtain a mesoporous UiO-67-coated Zn or Cu particle catalyst.

[0017] Furthermore, in step (1), the amine polar organic solvent is one of N,N-dimethylformamide and N,N-diethylformamide.

[0018] Furthermore, in the step (1), the ratio of zinc chloride or copper chloride, polyvinyl pyrrolidone, and amine polar organic solvent in the first mixed solution is 10-20 mmol: 30-80 mmol: 10 ml; and the ratio of ascorbic acid and amine polar organic solvent in the second mixed solution is 20-50 mmol: 10 ml.

[0019] Furthermore, in the step (1), the stirring condition is: 100-300 r / min; the washing condition is: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; the vacuum drying condition is: drying temperature 50-70°C, drying time 1-3h.

[0020] Furthermore, in step (2), the ratio of Zn or Cu particles, 4,4'-biphenyldicarboxylic acid, polyvinyl pyrrolidone, and N,N-dimethylformamide in the third mixed solution is: 3.0-13.0 mg: 0.08-0.12 mmol: 0.04-0.12 mmol: 10 ml; the ratio of zirconium oxychloride or hafnium oxychloride and N,N-dimethylformamide in the fourth mixed solution is: 0.04-0.08 mmol: 10 ml.

[0021] Furthermore, in step (2), the closed reaction conditions are: reaction temperature 100-150°C, reaction time 36-48h.

[0022] Furthermore, in the steps (2) and (3), the washing conditions are: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; and the vacuum drying conditions are: drying temperature 50-100° C., and drying time 1-6 h.

[0023] Furthermore, in step (3), the pore-forming agent solution is a sodium citrate aqueous solution or a sodium acetate aqueous solution.

[0024] Furthermore, in the step (3), the solvent thermal conditions are: reaction temperature 50-90° C., reaction time 3-6 h.

[0025] Furthermore, in the step (3), the amount of UiO-67 coated Zn or Cu particles added is 0.1-0.3 g / ml based on the amount of water in the pore former solution; and the amount of pore former added is 0.3-1 mmol / ml based on the amount of water in the pore former solution.

[0026] Furthermore, another object of the present invention is to provide an application of a mesoporous UiO-67-coated Zn or Cu particle catalyst prepared by the above method, and the specific application steps are as follows:

[0027] The mesoporous UiO-67-coated Zn or Cu particle catalyst is vacuum activated at 80-150° C. for 12-24 hours, ethylene dichloride, the activated catalyst and 2,6-di-tert-butyl-4-methylphenol are added to a reactor, and the reaction is carried out at 60-80° C. for 2-4 hours. After the reaction is completed, the mesoporous UiO-67-coated Zn or Cu particle catalyst and the reaction mother liquor are obtained by centrifugation, the reaction mother liquor is detected by gas chromatography to evaluate the catalytic effect, and the mesoporous UiO-67-coated Zn or Cu particle catalyst is repeatedly regenerated;

[0028] The ratio of the activated mesoporous UiO-67 coated Zn or Cu particle catalyst, dichloroethylene carbonate, and 2,6-di-tert-butyl-4-methylphenol is 1g: 2-3ml: 0.02-0.15g;

[0029] The repeated regeneration conditions of the mesoporous UiO-67-wrapped Zn or Cu particle catalyst are as follows: vacuum drying temperature of 100-150° C. and drying time of 12-24 hours.

[0030] The beneficial effects of the present invention are:

[0031] (1) A method for preparing a mesoporous UiO-67-encapsulated Zn or Cu particle catalyst of the present invention has the advantages of simple process, mild reaction, good repeatability and low energy consumption.

[0032] (2) The mesoporous UiO-67 of the present invention wraps the Zn or Cu particle catalyst, wherein UiO-67 is a shell layer, and the Zn or Cu metal particles are completely wrapped inside and evenly distributed by UiO-67, thereby improving the acid resistance and agglomeration resistance of the metal particles, thereby improving the catalytic activity.

[0033] (3) The present invention precisely controls the size, morphology and uniformity of Zn or Cu particles by controlling the concentrations of ascorbic acid and polyvinyl pyrrolidone; controls the concentrations and reaction time of metal cation salts, organic ligands and polyvinyl pyrrolidone, especially the effect of polyvinyl pyrrolidone, thereby controlling the particle size of UiO-67; and achieves a solvothermal etching reaction of UiO-67 by utilizing the synergistic effect of the pore-forming agent and water to obtain a mesoporous structure.

[0034] (4) The present invention uses Zn or Cu particles as seeds, then adds polyvinyl pyrrolidone, organic ligands, and metal cation salts, and then synthesizes UiO-67 encapsulated Zn or Cu particle catalysts in situ by solvent thermal reaction, and finally performs solvent thermal etching reaction in a pore-forming agent solution to obtain a mesoporous UiO-67 encapsulated Zn or Cu particle catalyst for the first time. The catalyst size is 1-2.5 μm, the pore size range is 5-50 nm, the Zn or Cu particle size is 20-70 nm, and the Zn or Cu particles account for 3-8% of the catalyst mass. We used TEM, SEM, XRD, N 2 -BET characterization method found that this method did not change the morphology and framework structure of UiO-67 itself. In addition, polyvinyl pyrrolidone not only has the function of adjusting the size of UiO-67 during the in-situ synthesis process, but also has the function of adsorbing zirconium or hafnium metal as the nucleation site of UiO-67.

[0035] (5) The mesoporous UiO-67 coated Zn or Cu particle catalyst of the present invention is applied to the catalytic field of vinyl dichlorocarbonate. By utilizing the synergistic effect of the UiO-67 mesoporous structure, the Zn or Cu particles, and the solvent thermal etching reaction process to expose more active sites of the catalyst, the preparation of vinyl carbonate from vinyl dichlorocarbonate in the absence of solvent is achieved. The conversion rate of vinyl dichlorocarbonate is 85-91.3%, the selectivity of vinyl carbonate is 95-99%, and the yield of vinyl carbonate is 84.2-89.1%. The mesoporous UiO-67 coated Zn or Cu particle catalyst has high catalytic stability and can be recycled. The catalytic performance remains basically unchanged after ten cycles, and no metal ions enter the vinyl carbonate.

[0036] (6) The catalytic application of dichloroethylene carbonate in the present invention solves the problem of recycling dichloroethylene carbonate, a byproduct in the process of preparing chloroethylene carbonate from ethylene carbonate, and changes the traditional method of treating dichloroethylene carbonate as a byproduct as solid waste. It increases the value of the product, optimizes the production process of ethylene carbonate and chlorine, and has no environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a transmission electron microscope (TEM) image of the Zn particles obtained in step (1) of Example 1;

[0038] Figure 2 TEM image of UiO-67 coated Zn particles obtained in step (2) of Example 1;

[0039] Figure 3 is a scanning electron microscope (SEM) image of the UiO-67-coated Zn particles obtained in step (2) of Example 1;

[0040] Figure 4This is a SEM image of the mesoporous UiO-67-encapsulated Zn particle catalyst obtained in step (3) of Example 1;

[0041] Figure 5 The X-ray diffraction (XRD) patterns of the Zn particles and the mesoporous UiO-67-encapsulated Zn particle catalyst obtained in steps (1) and (3) in Example 1, respectively;

[0042] Figure 6 The NLDFT model pore size distribution diagram of the mesoporous UiO-67 coated Zn or Cu particle catalyst obtained in step (3) of Examples 1-4, the mesoporous UiO-67 loaded Zn particle catalyst obtained in Comparative Example 3, the UiO-67 coated Zn particle catalyst obtained in Comparative Example 4, the UiO-67 coated Zn particle catalyst obtained in Comparative Example 5, and the catalyst in Comparative Example 7. The NLDFT model pore size distribution diagram is obtained by nitrogen total adsorption at 77K (N 2 -BET) test results;

[0043] Figure 7 The mesoporous UiO-67 coated Zn or Cu particle catalyst obtained in Examples 1-4 and the Zn particles, ZnO particles, mesoporous UiO-67 loaded Zn particle catalyst, UiO-67 coated Zn particle catalyst, UiO-67 coated Zn particle catalyst, UiO-67, and catalyst obtained in Comparative Examples 1-6 are used for the catalytic effect result of preparing vinylene carbonate from ethylene dichloride carbonate;

[0044] Figure 8 The stability test results of the mesoporous UiO-67 encapsulated Zn or Cu particle catalysts obtained in Examples 1-4, the mesoporous UiO-67 loaded Zn particle catalysts obtained in Comparative Example 3, and the catalyst obtained in Comparative Example 7;

[0045] Fig. 9 This is the SEM image of Zn particles obtained in Comparative Example 1;

[0046] Fig.10 TEM and XRD diagrams of ZnO particles obtained in Comparative Example 2; Note: Fig.10 (a) TEM image of ZnO particles. Fig.10 (b) is the XRD pattern of ZnO particles;

[0047] Fig.11 This is the TEM image of the mesoporous UiO-67 loaded Zn particle catalyst obtained in step (3) of comparative example 3. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited thereto. Example 1

[0049] (1) Dissolve 300 mmol zinc chloride and 1200 mmol polyvinyl pyrrolidone in 200 ml N,N-dimethylformamide (DMF), mix them uniformly by ultrasonication, and prepare a first mixed solution; dissolve 800 mmol ascorbic acid in 200 ml DMF, mix them uniformly by ultrasonication, and prepare a second mixed solution; add the second mixed solution to the first mixed solution, react at room temperature and 200 r / min for 1 h, wash with DMF and acetone four times respectively, and vacuum dry at 60°C for 2 h to obtain Zn particles;

[0050] (2) 1.25 g Zn particles, 20 mmol 4,4'-biphenyldicarboxylic acid, and 20 mmol polyvinyl pyrrolidone were added to 2000 ml DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol zirconium oxychloride was ultrasonically dissolved in 2000 ml DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, and transferred to a high-pressure reactor, and reacted at 120°C for 42 hours. After the reaction, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 hours to obtain UiO-67-coated Zn particles;

[0051] (3) 80 mmol of sodium citrate was added to 100 ml of water to prepare a pore-forming agent solution, and then 20 g of UiO-67-coated Zn particles were added to the pore-forming agent solution and reacted at 70°C for 5 h. After the reaction, the particles were centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 h to obtain a mesoporous UiO-67-coated Zn particle catalyst, which had a white powder appearance.

[0052] In Example 1, the Zn particles were subjected to transmission electron microscopy (TEM) morphology and X-ray diffraction (XRD) structure tests, and the results were as follows: Figure 1 , Figure 5 ; UiO-67 encapsulated Zn particles were subjected to TEM morphology and scanning electron microscopy (SEM) morphology tests, respectively. Figure 2 , Figure 3 ; SEM morphology, XRD structure, and nitrogen adsorption of mesoporous UiO-67-coated Zn particle catalyst (N 2 -BET) pore size distribution test, see Figure 4 , Figure 5 , Figure 6 ; The Zn metal ion content in the mesoporous UiO-67 encapsulated Zn particle catalyst was detected by inductively coupled plasma spectrometer (ICP).

[0053] The method for ICP detection of Zn metal ion content in mesoporous UiO-67 encapsulated Zn particle catalyst is as follows: 1) Prepare standard curves of different concentrations with Zn standard solution, and the average error is ≥0.999; 2) Weigh 10 mg of mesoporous UiO-67 encapsulated Zn particle catalyst and add it to 5 ml of aqua regia (the volume ratio of hydrochloric acid to nitric acid is 3:1) and ultrasonically dissolve it completely, then add 45 ml of pure water to obtain a test sample. The Zn metal ion content concentration of the test sample is obtained through the standard curve, and then the mass fraction of Zn particles in the mesoporous UiO-67 encapsulated Zn particle catalyst is obtained.

[0054] Depend on Figure 1 It can be seen that the Zn particles are spherical and the particle size is about 50nm; Figure 2 It can be seen that the size of the Zn particles wrapped by UiO-67 is 1.8μm, the Zn particles are located inside UiO-67, and UiO-67 is the shell layer. The size of the Zn particles is about 50nm. The size of the Zn particles before and after wrapping is about 50nm. Therefore, the solvent thermal reaction has little effect on the size of the Zn particles, indicating that it is a mild preparation method; Figure 3 It can be seen that the surface of the Zn particles wrapped by UiO-67 is very smooth, and no particles are observed, which further proves that UiO-67 completely wraps the Zn particles (Zn particles are the core and UiO-67 is the shell).

[0055] Depend on Figure 4 and Figure 5 It can be seen that the mesoporous UiO-67-wrapped Zn particle catalyst retains the octahedral morphology and framework structure of UiO-67, indicating that it is a mild preparation method; Figure 6 It can be seen that after the UiO-67-wrapped Zn particles are subjected to the solvent-thermal etching reaction of the pore-forming agent solution, mesopores are generated on the surface of UiO-67 with a pore size range of 9-45nm; ICP detection shows that Zn particles account for 6.0% of the mass of the mesoporous UiO-67-wrapped Zn particle catalyst.

[0056] The mesoporous UiO-67 coated Zn particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:

[0057] ① 20 g of mesoporous UiO-67-coated Zn particle catalyst was vacuum activated at 120°C for 18 h to obtain an activated mesoporous UiO-67-coated Zn particle catalyst;

[0058] ② Add 10g activated mesoporous UiO-67 coated Zn particle catalyst, 25ml dichloroethylene carbonate, and 1g 2,6-di-tert-butyl-4-methylphenol (BHT) into the reactor and react at 75°C for 3h;

[0059] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated Zn particle catalyst and the reaction mother liquid, and then use gas chromatography (GC) to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;

[0060] ④ The mesoporous UiO-67-encapsulated Zn particle catalyst was vacuum dried at 120° C. for 18 h, and the mesoporous UiO-67-encapsulated Zn particle catalyst was recovered.

[0061] Application of mesoporous UiO-67 coated Zn particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate. The catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated Zn particle catalyst, see Figure 8 .

[0062] The catalytic effect of mesoporous UiO-67 coated Zn particle catalyst - the conversion rate of ethylene dichloride was evaluated by gas chromatography (GC). The operation method was as follows: ethylene dichloride carbonate and chromatographic grade acetonitrile were used to prepare ethylene dichloride carbonate standard curves of different concentrations, with an average error of ≥0.999. The concentration of the test sample was obtained according to the ethylene dichloride carbonate standard curve, and then the conversion rate was obtained.

[0063] The GC evaluation of the catalytic effect of mesoporous UiO-67 coated Zn particle catalyst - the selectivity of vinylene carbonate was performed as follows: according to the peak area normalization method, the dichloroethylene carbonate reactant peak, 2,6-di-tert-butyl-4-methylphenol (BHT) peak, and solvent peak were deducted, and the ratio of the vinylene carbonate peak area to the remaining peak area was the selectivity.

[0064] Stability test method of mesoporous UiO-67 coated Zn particle catalyst: Repeat steps ②-④ with the recovered mesoporous UiO-67 coated Zn particle catalyst.

[0065] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 90.5%, the selectivity of vinylene carbonate is 98.5%, and the yield of vinylene carbonate is 89.1%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated Zn particle catalyst after ten cycles are 90.5% and 98.4% on average, respectively. It has high cycle stability and can be recycled repeatedly. Example 2

[0066] (1) Dissolve 200 mmol zinc chloride and 600 mmol polyvinyl pyrrolidone in 200 ml DMF, mix them evenly by ultrasonication, and prepare a first mixed solution; dissolve 400 mmol ascorbic acid in 200 ml DMF, mix them evenly by ultrasonication, and prepare a second mixed solution; add the second mixed solution to the first mixed solution, react at room temperature and 300 r / min for 0.5 h, wash with DMF and acetone three times respectively, and vacuum dry at 50°C for 3 h to obtain Zn particles;

[0067] (2) 0.75 g Zn particles, 20 mmol 4,4'-biphenyldicarboxylic acid, and 10 mmol polyvinyl pyrrolidone were added to 2500 ml DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol zirconium oxychloride was ultrasonically dissolved in 2500 ml DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, and transferred to a high-pressure reactor, and reacted at 100°C for 48 hours. After the reaction was completed, the mixture was centrifuged, washed three times with DMF and acetone respectively, and vacuum dried at 50°C for 6 hours to obtain UiO-67-coated Zn particles;

[0068] (3) 60 mmol of sodium citrate was added to 200 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-coated Zn particles were added to the pore-forming agent solution and reacted at 50 °C for 6 h. After the reaction, the particles were centrifuged, washed three times with DMF and acetone respectively, and vacuum dried at 50 °C for 6 h to obtain a mesoporous UiO-67-coated Zn particle catalyst.

[0069] The mesoporous UiO-67-wrapped Zn particle catalyst obtained in this embodiment has UiO-67 as a shell layer and Zn particles as a core. The size of the mesoporous UiO-67-wrapped Zn particle catalyst is about 1 μm, the appearance of the catalyst is a white powder, the pore size of the catalyst ranges from 5 to 30 nm, the size of the Zn particles is about 20 nm, and the Zn particles account for 3% of the mass of the mesoporous UiO-67-wrapped Zn particle catalyst.

[0070] The mesoporous UiO-67 coated Zn particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:

[0071] ① 20 g of mesoporous UiO-67-coated Zn particle catalyst was vacuum activated at 80°C for 24 h to obtain an activated mesoporous UiO-67-coated Zn particle catalyst;

[0072] ② Add 10g activated mesoporous UiO-67 coated Zn particle catalyst, 20ml dichloroethylene carbonate, and 0.2g BHT into the reactor and react at 60°C for 4h;

[0073] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated Zn particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;

[0074] ④ The mesoporous UiO-67-encapsulated Zn particle catalyst was vacuum dried at 100° C. for 24 h, and the mesoporous UiO-67-encapsulated Zn particle catalyst was recovered.

[0075] Application of mesoporous UiO-67 coated Zn particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate. The catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated Zn particle catalyst, see Figure 8 .

[0076] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated Zn particle catalyst and the stability test method of the mesoporous UiO-67 coated Zn particle catalyst are the same as those in Example 1.

[0077] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 85.0%, the selectivity of vinylene carbonate is 99.0%, and the yield of vinylene carbonate is 84.2%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated Zn particle catalyst remain basically unchanged after being recycled ten times, with an average of 85% and 98.9% respectively. It has strong cyclic stability and can be recycled repeatedly. Example 3

[0078] (1) Dissolve 400mmol zinc chloride and 1600mmol polyvinyl pyrrolidone in 200ml DMF and mix them evenly by ultrasonic to prepare a first mixed solution; dissolve 1000mmol ascorbic acid in 200ml DMF and mix them evenly by ultrasonic to prepare a second mixed solution; add the second mixed solution to the first mixed solution, react at room temperature and 100r / min for 2h, wash with DMF and acetone five times respectively, and vacuum dry at 70°C for 1h to obtain Zn particles;

[0079] (2) 1.625 g Zn particles, 15 mmol 4,4'-biphenyldicarboxylic acid, and 15 mmol polyvinyl pyrrolidone were added to 1250 ml DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol zirconium oxychloride was ultrasonically dissolved in 1250 ml DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, and transferred to a high-pressure reactor, and reacted at 150°C for 36 hours. After the reaction was completed, the mixture was centrifuged, washed with DMF and acetone five times each, and vacuum dried at 100°C for 1 hour to obtain UiO-67-coated Zn particles;

[0080] (3) 66.67 mmol of sodium citrate was added to 66.67 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-coated Zn particles were added to the pore-forming agent solution and reacted at 90 °C for 3 h. After the reaction, the catalyst was centrifuged, washed five times with DMF and acetone respectively, and vacuum dried at 100 °C for 1 h to obtain a mesoporous UiO-67-coated Zn particle catalyst.

[0081] The mesoporous UiO-67-wrapped Zn particle catalyst obtained in this embodiment has UiO-67 as a shell layer and Zn particles as a core. The size of the mesoporous UiO-67-wrapped Zn particle catalyst is about 2.5 μm, the appearance of the catalyst is white powder, the pore size of the catalyst ranges from 10 to 50 nm, the size of the Zn particles is about 70 nm, and the Zn particles account for 8.0% of the mass of the mesoporous UiO-67-wrapped Zn particle catalyst.

[0082] The mesoporous UiO-67 coated Zn particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:

[0083] ① 20 g of mesoporous UiO-67-coated Zn particle catalyst was vacuum activated at 150°C for 12 h to obtain an activated mesoporous UiO-67-coated Zn particle catalyst;

[0084] ② Add 10g activated mesoporous UiO-67 coated Zn particle catalyst, 30ml dichloroethylene carbonate, and 1.5g BHT into the reactor and react at 80°C for 2h;

[0085] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated Zn particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;

[0086] ④ The mesoporous UiO-67-encapsulated Zn particle catalyst was vacuum dried at 150° C. for 12 h, and the mesoporous UiO-67-encapsulated Zn particle catalyst was recovered.

[0087] Application of mesoporous UiO-67 coated Zn particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate. The catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated Zn particle catalyst, see Figure 8 .

[0088] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated Zn particle catalyst and the stability test method of the mesoporous UiO-67 coated Zn particle catalyst are the same as those in Example 1.

[0089] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 91.3%, the selectivity of vinylene carbonate is 95%, and the yield of vinylene carbonate is 86.7%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated Zn particle catalyst remain basically unchanged after being recycled ten times, with an average of 91.2% and 95.0% respectively. It has strong cyclic stability and can be recycled repeatedly. Example 4

[0090] (1) Dissolve 300 mmol copper chloride and 1400 mmol polyvinyl pyrrolidone in 200 ml N,N-diethylformamide (DEF), mix them evenly by ultrasonication, and prepare a first mixed solution; dissolve 1000 mmol ascorbic acid in 200 ml DEF, mix them evenly by ultrasonication, and prepare a second mixed solution; add the second mixed solution to the first mixed solution, react at room temperature and 200 r / min for 1 h, wash with DMF and acetone five times each, and vacuum dry at 60°C for 1.5 h to obtain Cu particles;

[0091] (2) 1.25 g of Cu particles, 20 mmol of 4,4'-biphenyldicarboxylic acid, and 16 mmol of polyvinyl pyrrolidone were added to 2000 ml of DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol of hafnium oxychloride was ultrasonically dissolved in 2000 ml of DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, and transferred to a high-pressure reactor, and reacted at 120°C for 48 hours. After the reaction was completed, the mixture was centrifuged, washed with DMF and acetone five times each, and vacuum dried at 100°C for 2 hours to obtain UiO-67-coated Cu particles;

[0092] (3) 85 mmol of sodium acetate was added to 100 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-coated Cu particles were added to the pore-forming agent solution and reacted at 80 °C for 4 h. After the reaction, the catalyst was centrifuged, washed five times with DMF and acetone respectively, and vacuum dried at 100 °C for 2 h to obtain a mesoporous UiO-67-coated Cu particle catalyst.

[0093] The mesoporous UiO-67-wrapped Cu particle catalyst obtained in this embodiment has UiO-67 as a shell layer and Cu particles as a core. The size of the mesoporous UiO-67-wrapped Cu particle catalyst is 1.8 μm, the appearance of the catalyst is a white powder, the pore size of the catalyst ranges from 8 to 42 nm, the size of the Cu particles is 60 nm, and the Cu particles account for 6.0% of the mass of the mesoporous UiO-67-wrapped Cu particle catalyst.

[0094] The mesoporous UiO-67 coated Cu particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:

[0095] ① 20 g of mesoporous UiO-67-coated Cu particle catalyst was vacuum activated at 150°C for 12 h to obtain an activated mesoporous UiO-67-coated Cu particle catalyst;

[0096] ② Add 10g activated mesoporous UiO-67 coated Cu particle catalyst, 25ml dichloroethylene carbonate, and 1g BHT into the reactor and react at 75°C for 3h;

[0097] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated Cu particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;

[0098] ④ The mesoporous UiO-67-encapsulated Cu particle catalyst was vacuum dried at 150° C. for 12 h, and the mesoporous UiO-67-encapsulated Cu particle catalyst was recovered.

[0099] Application of mesoporous UiO-67 coated Cu particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate. The catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated Cu particle catalyst, see Figure 8 .

[0100] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated Cu particle catalyst and the stability test method of the mesoporous UiO-67 coated Cu particle catalyst are the same as those in Example 1.

[0101] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 90.0%, the selectivity of vinylene carbonate is 98.0%, and the yield of vinylene carbonate is 88.2%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated Cu particle catalyst remain basically unchanged after being recycled ten times, with an average of 89.5% and 97.0% respectively. It has strong cyclic stability and can be recycled repeatedly. Comparative Example 1

[0102] The Zn particles were prepared in the same manner as in Example 1, but without adding polyvinyl pyrrolidone. The Zn particles were tested by SEM. Fig. 9 .

[0103] The Zn particles are used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in FIG. Figure 7 .

[0104] Depend on Fig. 9 and Figure 1 By comparison, it can be seen that when there is no polyvinyl pyrrolidone, the Zn particles are irregular and uneven in shape, such as spheres and rods, and the size of the Zn particles is about 25nm. Therefore, polyvinyl pyrrolidone affects the morphology, uniformity and particle size of the Zn particles.

[0105] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate of Zn particles is 98.0%, the selectivity of vinylene carbonate is 80.0%, and the yield of vinylene carbonate is 78.4%. However, during the experiment, it was found that Zn particles dissolved in dichloroethylene carbonate and could not be recycled, resulting in zero utilization of the catalyst. In addition, since Zn impurity ions are in vinylene carbonate, they will affect the performance of the battery. Comparative Example 2

[0106] 300mmol zinc chloride and 1200mmol polyvinyl pyrrolidone were dissolved in 200ml N,N-dimethylformamide (DMF), and ultrasonically mixed to prepare a mixed solution. The solution was reacted at room temperature and 200r / min for 1h, washed four times with DMF and acetone respectively, and vacuum dried at 60°C for 2h to obtain zinc oxide particles.

[0107] The zinc oxide particles were tested by TEM morphology and XRD structure. Fig.10 .

[0108] The zinc oxide particles are used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in FIG. Figure 7 .

[0109] Depend on Fig.10 It can be seen that the morphology of the particles is amorphous, and the XRD test confirms that the structure of the particles is zinc oxide. Therefore, ascorbic acid is the key to the formation of Zn particles and can affect the morphology of the particles.

[0110] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate of ZnO particles is 45.5%, the selectivity of vinylene carbonate is 95.0%, and the yield of vinylene carbonate is 41.0%. However, it was found during the experiment that ZnO particles were partially dissolved in dichloroethylene carbonate, and it was impossible to fully recycle the ZnO particles, resulting in a decrease in the utilization rate of the catalyst. In addition, since Zn impurity ions are in vinylene carbonate, they will affect the performance of the battery. Comparative Example 3

[0111] (1) Zn particles were prepared in the same manner as in Example 1;

[0112] (2) 1.25 g Zn particles and 20 mmol 4,4'-biphenyldicarboxylic acid were added to 2000 ml DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol zirconium oxychloride was ultrasonically dissolved in 2000 ml DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, transferred to a high-pressure reactor, and reacted at 120°C for 42 hours. After the reaction was completed, the catalyst was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 hours to obtain a UiO-67-loaded Zn particle catalyst;

[0113] (3) 80 mmol of sodium citrate was added to 100 ml of water to prepare a pore-forming agent solution, and then 20 g of UiO-67-loaded Zn particle catalyst was added to the pore-forming agent solution and reacted at 70°C for 5 h. After the reaction, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 h to obtain a mesoporous UiO-67-loaded Zn particle catalyst.

[0114] The TEM morphology of the mesoporous UiO-67 supported Zn particle catalyst was tested. Fig.11 ; N 2 -BET pore size distribution test, see Figure 6 .

[0115] Depend on Fig.11 It can be seen that the Zn particles are located on the surface of UiO-67, and the Zn particles are the shell layer. Therefore, polyvinyl pyrrolidone not only has the function of adjusting the size of UiO-67 during the in-situ synthesis process, but also has the function of adsorbing zirconium or hafnium metal as the nucleation site of UiO-67, which is the key to preparing the UiO-67 completely encapsulated Zn particle catalyst.

[0116] Depend on Figure 6 It can be seen that the pore size range of the mesoporous UiO-67 loaded Zn particle catalyst is 2-30 nm; compared with Example 1, it can be seen that the surface loaded Zn particles will affect the solvent thermal etching reaction, resulting in a smaller pore size.

[0117] The mesoporous UiO-67 supported Zn particle catalyst is used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as those in Example 1. The catalytic effect is shown in FIG. Figure 7 .

[0118] The stability test of the mesoporous UiO-67 supported Zn particle catalyst was carried out in the same manner as in Example 1. The stability test results are shown in Figure 8 .

[0119] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate of the mesoporous UiO-67 supported Zn particle catalyst is 83.5%, the selectivity of vinylene carbonate is 88.0%, and the yield of vinylene carbonate is 73.5%. Therefore, the catalytic effect is not only related to the pore size, but also to the position of the Zn particles.

[0120] Depend on Figure 8 It can be seen that the catalytic efficiency of the mesoporous UiO-67 loaded Zn particle catalyst gradually decreased. After ten cycles, the catalytic effect was 72.0% conversion rate of ethylene dichloride carbonate and 89.5% selectivity of vinylene carbonate. We found that this was due to the surface loading of Zn particles, which led to the partial dissolution of the Zn particles loaded on the surface of mesoporous UiO-67 in an acidic environment; in addition, due to the high temperature desorption and regeneration of the mesoporous UiO-67 loaded Zn particle catalyst, some Zn particles would agglomerate, further leading to a decrease in the catalytic effect. Comparative Example 4

[0121] Comparative Example 4 is the same as steps (1) and (2) of Example 1, except that no sodium citrate is added in step (3).

[0122] The UiO-67 coated Zn particle catalyst obtained in step (3) was subjected to N 2 -BET pore size distribution test, see Figure 6 .

[0123] Depend on Figure 6 It can be seen that the pore size range of the UiO-67 coated Zn particle catalyst is 1-20nm, belonging to a multi-level pore structure of micropores and mesopores. Compared with Example 1, it can be seen that sodium citrate affects the formation of the mesoporous structure on the surface of UiO-67.

[0124] The UiO-67 coated Zn particle catalyst is used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as those in Example 1. The catalytic effect is shown in FIG. Figure 7 .

[0125] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 70.5%, the selectivity of vinylene carbonate is 98.5%, and the yield of vinylene carbonate is 69.4%. It can be seen that the pore size affects the catalytic effect. Comparative Example 5

[0126] Comparative Example 5 is the same as steps (1) and (2) of Example 1, except that in step (3), the solvent in the pore-forming agent solution is different, and water is replaced by DMF.

[0127] The UiO-67 coated Zn particle catalyst obtained in step (3) was subjected to N 2 -BET pore size distribution test, see Figure 6 .

[0128] Depend on Figure 6 It can be seen that the pore size range of the UiO-67-wrapped Zn particle catalyst is 1-3 nm. Combining Example 1 with Comparative Example 4, it can be seen that sodium citrate and water have a synergistic effect, and the two together realize the solvent-thermal etching reaction on the surface of UiO-67, and water is the key factor in the etching reaction to form pores.

[0129] The UiO-67 coated Zn particle catalyst was used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps were the same as in Example 1. The catalytic effect was shown in FIG. Figure 7 .

[0130] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 60.0%, the selectivity of vinylene carbonate is 98.5%, and the yield of vinylene carbonate is 59.1%. In combination with Example 1, it can be seen that the mesoporous structure has an important influence on the catalysis of dichloroethylene carbonate, and the macromolecular particles can enter the interior of the catalyst and are no longer limited to the catalyst surface. At the same time, the solvent thermal etching reaction can expose more reaction sites of the catalyst, thereby improving the catalytic activity. Comparative Example 6

[0131] 20mmol 4,4'-biphenyldicarboxylic acid and 20mmol polyvinyl pyrrolidone were added to 2000ml DMF and ultrasonically mixed to prepare a first mixed solution; 10mmol zirconium oxychloride was ultrasonically dissolved in 2000ml DMF to prepare a second mixed solution; the second mixed solution was added to the first mixed solution, transferred to a high-pressure reactor, and reacted at 120°C for 42h. After the reaction, centrifugation, DMF and acetone washing were performed four times respectively, and vacuum drying was performed at 80°C for 3h to obtain UiO-67.

[0132] UiO-67 is used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in Figure 7 .

[0133] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate of pure UiO-67 is 53.0%, the selectivity of vinylene carbonate is 99.5%, and the yield of vinylene carbonate is 52.7%. In combination with Example 1, Comparative Example 1, and Comparative Example 3, it can be seen that the catalytic effect is related to the pore size and the position of the Zn particles. The pore size and the position of the Zn particles (loaded or fully wrapped) mainly affect the conversion rate and purity, and the position of the Zn particles (loaded or fully wrapped) affects the stability and service life, that is, the mesoporous structure on the surface of UiO-67 and the Zn particles inside UiO-67 synergistically catalyze the conversion of dichloroethylene carbonate to vinylene carbonate. Comparative Example 7

[0134] Comparative Example 7 is the same as steps (1) and (3) of Example 1, except that the amount of Zn particles used in step (2) is different, from 1.25 g to 3.0 g.

[0135] The catalyst obtained in step (3) is used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as those in Example 1. The catalytic effect is shown in Figure 7 .

[0136] The catalyst obtained in step (3) was tested for pore size distribution and stability using the same testing methods as in Example 1. Figure 6 , Figure 8 .

[0137] Depend on Figure 6 and Figure 7It can be seen that the pore size range of the catalyst is 5-30nm, which belongs to a mesoporous structure, the conversion rate of dichloroethylene carbonate is 90.0%, the selectivity of vinyl carbonate is 90%, and the yield of vinyl carbonate is 81%; compared with Example 1, it can be seen that the catalytic effect of the catalyst in Comparative Example 7 is poor. This is because there are too many Zn particles, resulting in UiO-67 not completely wrapping the Zn particles during the in-situ synthesis process. The surface of UiO-67 is loaded with some Zn particles, which in turn affects the etching effect in the solvent thermal etching reaction. Therefore, it is necessary to accurately add the amount of Zn particles to avoid affecting the solvent thermal etching reaction, in-situ synthesis, and subsequent catalysis.

[0138] Depend on Figure 8 It can be seen that the cyclic stability of the catalyst is poor. After ten cycles, the conversion rate of dichloroethylene carbonate is 75.0% and the selectivity of vinyl carbonate is 94%, which further shows that the catalyst surface contains Zn particles. It can be seen that the Zn particles on the surface will affect the selectivity and conversion rate of the catalytic effect, and more importantly, affect the service life of the catalyst, especially in an acidic environment. Zn will enter the target product vinyl carbonate, and Zn impurity ions will affect the performance of vinyl carbonate in the battery field.

[0139] From the above, it can be seen that ascorbic acid is the key to the formation of Zn or Cu metal particles; polyvinyl pyrrolidone not only affects the morphology, uniformity and size of Zn or Cu particles, but also adjusts the size of UiO-67, and is a key factor in the formation of UiO-67 completely encapsulating Zn or Cu particles; the pore-forming agent solution is the key to the formation of mesoporous materials, and the formation of mesoporous structure is not only related to the pore-forming agent, but also to the solvent. The mesoporous structure is formed under the joint action of water and the pore-forming agent; the amount of Zn or Cu metal particles added will affect the degree of UiO-67 encapsulation of Zn or Cu metal particles and the surface pore size, and there is an optimal range of Zn or Cu metal particles added; the mesoporous structure on the surface of UiO-67 and the Zn or Cu metal particles inside UiO-67 have a synergistic catalytic effect on ethylene dichloride carbonate.

[0140] The above description is only a preferred embodiment of the present invention and cannot limit the scope of the present invention. That is, equivalent changes and modifications described in the scope of the present invention and the description should all fall within the scope of the present invention.

Claims

1. A mesoporous UiO-67 coated Zn or Cu particle catalyst, characterized in that: It is a white powder catalyst with Zn or Cu particles as the core and mesoporous UiO-67 as the shell structure; the pore size range is 5-50nm, the mesoporous UiO-67 completely wraps the Zn or Cu particles, the size of mesoporous UiO-67 is 1-2.5μm, the size of Zn or Cu particles is 20-70nm, and the Zn or Cu particles account for 3-8% of the catalyst mass; The preparation method of the mesoporous UiO-67-wrapped Zn or Cu particle catalyst comprises the following steps: (1) dissolving zinc chloride or copper chloride and polyvinyl pyrrolidone in an amine polar organic solvent and ultrasonically dissolving them to prepare a first mixed solution; dissolving ascorbic acid in an amine polar organic solvent and ultrasonically dissolving them to prepare a second mixed solution; adding the second mixed solution to the first mixed solution, stirring at room temperature for 0.5-2h, centrifuging, washing, and vacuum drying to obtain Zn or Cu particles; (2) adding Zn or Cu particles, 4,4'-biphenyldicarboxylic acid, and polyvinyl pyrrolidone to N,N-dimethylformamide, and uniformly mixing by ultrasonication to prepare a third mixed solution; dissolving zirconium oxychloride or hafnium oxychloride in N,N-dimethylformamide by ultrasonication to prepare a fourth mixed solution; adding the fourth mixed solution to the third mixed solution, and then reacting in a closed state; after the reaction is completed, centrifuging, washing, and vacuum drying to obtain UiO-67-coated Zn or Cu particles; (3) adding UiO-67-coated Zn or Cu particles into a pore-forming agent solution for solvothermal reaction, and after the reaction is completed, centrifuging, washing, and vacuum drying to obtain a mesoporous UiO-67-coated Zn or Cu particle catalyst; In the step (1), the amine polar organic solvent is one of N,N-dimethylformamide and N,N-diethylformamide; In the step (3), the pore-forming agent solution is a sodium citrate aqueous solution or a sodium acetate aqueous solution.

2. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the step (1), the ratio of zinc chloride or copper chloride, polyvinyl pyrrolidone, and amine polar organic solvent in the first mixed solution is 10-20 mmol: 30-80 mmol: 10 ml; The ratio of ascorbic acid to amine polar organic solvent in the second mixed solution is 20-50mmol:10ml.

3. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the step (1), the stirring condition is 100-300 r / min; the washing condition is washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; the vacuum drying condition is drying temperature 50-70°C and drying time 1-3h.

4. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the step (2), the ratio of Zn or Cu particles, 4,4'-biphenyldicarboxylic acid, polyvinyl pyrrolidone, and N,N-dimethylformamide in the third mixed solution is 3.0-13.0 mg: 0.08-0.12 mmol: 0.04-0.12 mmol: 10 ml; the ratio of zirconium oxychloride or hafnium oxychloride and N,N-dimethylformamide in the fourth mixed solution is 0.04-0.08 mmol: 10 ml.

5. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In step (2), the closed reaction conditions are: reaction temperature 100-150°C, reaction time 36-48h.

6. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the steps (2) and (3), the washing conditions are to use N,N-dimethylformamide and acetone as the washing agent for three to five times respectively; and the vacuum drying conditions are to have a drying temperature of 50-100° C. and a drying time of 1-6 hours.

7. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the step (3), the solvent thermal conditions are: reaction temperature 50-90°C, reaction time 3-6h.

8. The mesoporous UiO-67 coated Zn or Cu particle catalyst according to claim 1, characterized in that: In the step (3), the amount of UiO-67 coated Zn or Cu particles added is 0.1-0.3 g / ml based on the amount of water in the pore former solution; the amount of pore former added is 0.3-1 mmol / ml based on the amount of water in the pore former solution.

9. The use of the mesoporous UiO-67 coated Zn or Cu particle catalyst according to any one of claims 1 to 8, wherein the specific application steps are as follows: The mesoporous UiO-67-coated Zn or Cu particle catalyst is vacuum activated at 80-150° C. for 12-24 hours, ethylene dichloride, the activated catalyst and 2,6-di-tert-butyl-4-methylphenol are added to a reactor, and the reaction is carried out at 60-80° C. for 2-4 hours. After the reaction is completed, the mesoporous UiO-67-coated Zn or Cu particle catalyst and the reaction mother liquor are obtained by centrifugation, the reaction mother liquor is detected by gas chromatography to evaluate the catalytic effect, and the mesoporous UiO-67-coated Zn or Cu particle catalyst is repeatedly regenerated; The ratio of the activated mesoporous UiO-67 coated Zn or Cu particle catalyst, dichloroethylene carbonate, and 2,6-di-tert-butyl-4-methylphenol is 1g: 2-3ml: 0.02-0.15g; The repeated regeneration conditions of the mesoporous UiO-67-wrapped Zn or Cu particle catalyst are as follows: vacuum drying temperature of 100-150° C. and drying time of 12-24 hours.